The consulting Bible : everything you need to know to create and expand a seven-figure consulting practice - Weiss, Alan, 1946- (Hoboken, NJ : Wiley, 2011)
'Everything you need to know about building a successful, world-class consulting practice Whether you are a veteran consultant or new to the industry, an entrepreneur or the principal of a small firm, The Consulting Bible tells you absolutely everything you need to know to create and expand a seven-figure independent or boutique consulting practice. Expert author Alan Weiss, who coaches consultants globally and has written more books on solo consulting than anyone in history, shares his expertise comprehensively. Learn and appreciate the origins and evolution of the consulting profession. Launch your practice or firm and propel it to top performance. Implement your consulting strategies in public and private organizations, large or small, global or domestic. Select from the widest variety of consulting methodologies. Achieve lasting success in your professional career and personal goals. The author is recognized as'one of the most highly regarded independent consultants in America' by the New York Post and'a worldwide expert in executive education' by Success Magazine. Whether you're just starting out or looking for the latest trends in modern practice, The Consulting Bible gives you an unparalleled toolset to build a thriving consultancy.'--
Includes bibliographical references and index.
Keywords: Business consultants; Consultants -- Marketing